Actividad antibacteriana de diferentes extractos de Spondias mombin L. - Flores Reátegui, Adriana Daniela (2024)
The antibacterial activity of ethanolic and chloroformic extracts of leaves and bark of Spondias mombin L. was evaluated against bacterial strains Staphylococcus aureus ATCC 25923, Escherichia coli ATCC 25922, Pseudomonas aeruginosa ATCC 27853 and Salmonella typhimurium ATCC 14028. A descriptive experimental-analytical design was used. The plant samples were collected in the Allpahuayo Mishana National Reserve, Iquitos - Peru; they were dried and macerated in ethanol and chloroform to obtain the extracts. These were subjected to phytochemical screening and antibacterial sensitivity tests using the Kirby-Bauer method and macrodilution in broth. The results showed that the ethanolic extract of the bark presented a higher abundance of flavonoids and triterpenes, while the chloroplast extract of the leaves showed abundance of steroids and triterpenes. However, both extracts showed low antibacterial activity against the strains studied, with inhibition halos of less than 15 mm, with S. aureus being the most sensitive strain to the ethanolic extract of leaves at the concentration of 125 mg/mL. The study concludes that S. mombin L. extracts present limited antibacterial activity, suggesting the need for further research to explore their therapeutic potential. Keywords: Spondias mombin L., antibacterial activity, ethanolic extract, chloroplast extract, Staphylococcus aureus, phytochemical screening.